My best friend is invisible - Stine, R. L. (New York : Scholastic, 1997)
Sammy Jacobs sets out to find a way to get rid of his new invisible friend who begins hanging out in his room and eating his food.
3.8
5-8
Keywords: Fantasy; Horror stories; Imaginary playmates -- Fiction; Horror fiction; Imaginary playmates -- Fiction; Fantastic fiction